Alternative Mathematical Models for the Optimal Transmission Switching Problem - Flores, Moises (2020)
In this work, the Optimal Transmission Switching (OTS) problem is solved in order to optimize the operation cost of an electrical power system. This is accomplished by disconnecting some transmission lines, which enables a change to the profile of the power flow distribution in the system, allowing for increased generation at the buses with lower costs; thus, the hourly operation cost of the generation is minimized to meet the demand of the system. This paper presents contributions to topics related to the issue of the high number of transmission lines that are disconnected when the OTS problem is solved, the problem of system islanding, and the causes of Braess’s paradox, in the context of the OTS problem. Finally, tests are conducted using the 41-bus southern Brazilian system and the 92-bus Colombian system. The results demonstrate the effectiveness of the proposals for reducing the number of lines disconnected from the system and for avoiding islanding.